A cross-sectional study on frequency of rubber dam usage among dentists practicing in Maharashtra, India - Apeksha Mahendra Sanghvi; Rahul Javerchand Nagda; Padmini Jagdish Raju (Saudi Endodontic Journal, 2018)
Introduction: Rubber dam was introduced more than 150 years ago. It has been the standard of care, especially in endodontics. In spite of its advantages, dentists still refrain from using it. Hence, the objective of this study was to investigate the frequency of rubber dam usage among dental practitioners in Maharashtra, India. Materials and Methods: It was a cross-sectional study. The questions were regarding the usage of rubber dam in their practices which was answered by the dentists. A sample size of the study was 400. Questionnaire included eight questions and the last question was open-ended. Results: Dentists using the rubber dam in their daily practice were only 23.8%. Out of which, only 4.2% dentists use it in 100% of the cases. When the reason for not using the rubber dam was asked, 40% dentists said they do not use rubber dam because its time consuming, 37% do not use it due to patient compliance, 14% responded that it is expensive, and 9% were unsure of the technique. Conclusions: The low percentage of rubber dam usage in Maharashtra is not acceptable, and dentists should follow recommended standard of care. Dental schools should make it mandatory for students to use rubber dam in root canal treatments.